Analysis of Inventory Control by Using Economic Order Quantity Model – A Case Study in PT Semen Padang - Prima Fithri; Alizar Hasan; Fadhita Maisa Asri (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2019)
Inventory control is a very important issue. It is because the amount of inventory will determine or affect the smoothness of the production process as well as the effectiveness and efficiency of the company. PT Semen Padang is a manufacturing company that produces 10,400,000 tons of cement per year. The achievement of the cement production target at this company depends on the availability of raw materials needed in the cement production process itself. Gypsum is an additional material of the cement production process which is very important because it is a raw material that must exist in the process of making cement. So, if the inventory of gypsum cannot meet the needs of production, then the production process of cement making will be disrupted. PT Semen Padang is using the Min-Max method for inventory control. But the costs are quite high. The cost of inventory can be minimized by using another method such as EOQ (Economic Order Quantity). The conclusions of this research are in 2016 by using EOQ method, the optimal order quantity is 32,073 ton per order, and the frequency is 9 times in a year with total cost Rp. 4,757,673,813.48, and in 2017, the optimal order quantity is 34,856 tons per order and the frequency is 9 times in a year with total cost Rp. 9,694,805,608.36.